34. RESULTS OF ORAL ADMINISTRATION OF INTRAVENOUS OXYTOCIN IN PREGNANCY WOMEN IN TERM AT THAI NGUYEN A HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the clinical characteristics and evaluating results of intravenous  oxytocin in mothers who gave term birth at Thai Nguyen A Hospital in 2023 - 2024.Materials and methods: A cross-sectional descriptive study of mothers who gave term birth at Thai Nguyen A Hospital from August 2023 to March 2024.Results: We found 220 pregnancies were eligible for the criteria and were admitted to the study. The average age is 27,2 ± 2,17. The occupation of most pregnant women is employee. The rate of vaginal delivery was 82,7% . The rate of failed induction requiring cesarean section was 17,3%. The main cause of cesarean section is cervical dilation no progress (57,9%). 100% newborn infant had Apgar scores greater than 7.Conclusions: Intravenous oxytocin for the induction and augmention of labour is safe and high effective in term pregnancies.
Keywords: Intravenous oxytocin